Public charge in the time of coronavirus - Martha Tepepa (Levy Economics Institute of Bard College, 2020)
The United States government recently passed legislation and stabilization packages to respond to the COVID-19 (i.e., coronavirus disease 2019) outbreak by providing paid sick leave, tax credits, and free virus testing; expanding food assistance and unemployment benefits; and increasing Medicaid funding. However, the response to the global pandemic might be hindered by the lassitude of the state and the administration's conception of social policy that leaves the most vulnerable unprotected. The administration's "zero tolerance" immigration campaign poses public health challenges, especially in the prevention of communicable diseases. In addition to the systemic obstacles noncitizens face in their access to healthcare, recent changes to immigration law that penalize recipients of some social services on grounds that they are a public charge will further restrict their access to treatment and hinder the fight against the pandemic.
Keywords: H4; H55; H57; H75; H84; I38; O15; O51; Z18; 330; Public Charge; Public Services; Coronavirus; COVID-19; Social Policy; State; Means Testing; Public Assistance; Welfare Policy; Free Rider